Presenting a Social Media Marketing Model in the Banking Services Industry: A Mixed Methods Study - Fasihi Azar, Javad; Rousta, Alireza; Asayesh, Farzad (Management Strategies and Engineering Sciences, 2025)
This study aims to develop an indigenous social media marketing model tailored to the banking services industry in Iran through a mixed methods approach. In the qualitative phase, grounded theory methodology was employed to analyze data collected from 16 semi-structured interviews with marketing experts, digital banking professionals, and academic specialists. The data were coded using Strauss and Corbin’s three-stage process—open, axial, and selective coding—using MAXQDA software. The findings revealed six main categories, fourteen subcategories, and seventy-four indicators influencing social media marketing strategies. Based on these, a theoretical model was proposed, identifying causal conditions (social media-related factors, managerial factors, structural factors), strategic categories (marketing and human resource actions), contextual conditions (relationship marketing and ICT), intervening conditions (customer trust, perceived risk, environmental threats), and outcomes (awareness, perceived quality, customer satisfaction and trust, environmental opportunities and threats). In the quantitative phase, a researcher-developed questionnaire was distributed to 384 customers of Bank Mellat who use social media. The instrument's validity was confirmed through content validity index (CVI) and content validity ratio (CVR), and reliability was assessed via Cronbach’s alpha, composite reliability, and Fornell-Larcker criteria. Structural equation modeling using partial least squares (PLS) indicated significant relationships among the proposed variables. The findings underscore the importance of strategic, contextual, and organizational factors in enhancing the effectiveness of social media marketing in the banking sector. The study offers a comprehensive framework for banking institutions to optimize their digital marketing strategies and improve customer engagement, satisfaction, and trust.